Analisis Determinan Growth Failure (Stunting) pada Anak Usia 0 - 59 Bulan di Puskesmas Panjang Kota Bandar Lampung - Vivi Yolandha; Dina Dwi Nuryani; Vera Yulyani (Universitas Malahayati Lampung, 2024)
ABSTRACT Stunting in toddlers is a nutrition problem in the world today, especially in developing countries, including Indonesia. Based on the 2022 stunting population in Lampung Province of 15.2%. Puskesmas Panjang is one of the Puskesmas in Bandar Lampung with the highest stunting rate of 566 people (22.9%). The purpose of this study was to determine the determinants of growth failure (stunting) in children aged 0 - 59 months at Puskesmas Panjang, Bandar Lampung. Type of quantitative research with a case control approach. The scope of researchers at Puskesmas Panjang Health Center in Bandar Lampung. The research was conducted in May 2023. The population in the study were all mothers who had children aged 0 - 59 months, with a sample of 162 children. The variables in the study were early breastfeeding initiation, exclusive breastfeeding, complementary feeding, and environmental sanitation with the incidence of stunting. Data collection using questionnaires, data analysis by univariate (frequency distribution), bivariate (chi square) and multivariate (logistic regression). The results showed that there is a significant relationship with the incidence of stunting is Early Breastfeeding Initiation (p-value = 0.008; OR = 2.60), exclusive breastfeeding history (p-value = 0.000; OR = 4.98), history of complementary feeding (p-value = 0.001; OR = 3.20), Environmental Sanitation (p-value = 0.001; OR = 3.31). Exclusive breastfeeding is the dominant variable on the incidence of stunting in children (p-value = 0.001; OR = 4.027). Research suggestions are expected to educate and understand, counseling or installing posters to the community, especially pregnant women and mothers who have toddlers in the form of the importance of the role of exclusive breastfeeding for toddlers where exclusive breastfeeding affects the incidence of stunting in toddlers. Keywords: Stunting, Malnutrition, Growth and Development ABSTRAK Stunting pada balita merupakan permasalahan gizi di dunia saat ini terutama di negara-negara berkembang, termasuk indonesia. Berdasarkan populasi stunting tahun 2022 di Provinsi Lampung sebesar 15,2%. Puskesmas Panjang merupakan salah satu Puskesmas di Bandar Lampung dengan angka stunting tertinggi sebanyak 566 orang (22,9%). Tujuan penelitian ini adalah diketahui determinan growth failure (stunting) pada anak usia 0 – 59 bulan di Puskesmas Panjang Bandar Lampung. Jenis penelitian kuantitatif dengan pendekatan Case Control. Ruang lingkup peneliti di Puskesmas Panjang Bandar Lampung. Penelitian dilakukan bulan Mei 2023. Populasi dalam penelitian adalah seluruh ibu yang memiliki anak usia 0 - 59 bulan, dengan sampel 162 anak. Variabel dalam penelitian yaitu Inisiasi menyusui dini, ASI Eksklusif, MP-ASI, dan Sanitasi Lingkungan dengan kejadian stunting. Pengumpulan data menggunakan kuesioner, analisis data secara univariat (distribusi frekuensi), bivariat (chi square) dan multivariat (regresi logistik). Hasil penelitian didapatkan ada hubungan yang signifikan dengan kejadian stunting adalah Inisiasi Menyusui Dini (p–value = 0,008; OR = 2.60), riwayat pemberian ASI eksklusif (p–value = 0,000 ; OR = 4.98), riwayat pemberian MP-ASI (p–value = 0,001 ; OR = 3.20), Sanitasi Lingkungan (p–value = 0,001 ; OR = 3.31). Asi Eksklusif merupakan variabel dominan terhadap Kejadian Stunting pada anak ( p–value = 0,001 ; OR = 4.027). Saran penelitian diharapkan melakukan edukasi dan pemahaman, penyuluhan atau pemasangan poster kepada masyarakat terutama ibu hamil dan ibu yang memiliki balita berupa pentingnya peran ASI Eksklusif untuk balita diaman ASI Eksklusif berpengaruh terhadap kejadian stunting pada balita. Kata Kunci: Stunting, Gizi Buruk, Tumbuh Kembang